AKTUALISASI LITERASI BAHASA ARAB BAGI GURU PAI UNTUK MENUNJANG KOMPETENSI PAEDAGOGIK PERSPEKTIF UMAR BIN KHATTAB - Rochmat, Cecep Sobar; Susanti, Cela Petty; Maulaya, Rosendah Dwi (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2023)
The profile of Islamic education teachers is those who teach learners and society by referring to the Quran and Hadith as the main sources. Understanding and teaching the Qur'an and Hadith certainly requires mastery of Arabic literacy. Also, the scope of PAI material itself, be it Qur'anic Hadith, Jurisprudence, Akidah Akhlak and SKI lessons can never be separated from the use of Arabic word terms. As is known, Arabic is the heart of learning Islam. However, what if the teacher does not have Arabic literacy skills. Of course, PAI teachers will find it difficult to interpret PAI materials that correlate with the Qur'an and Sunnah. If the professionalism of mastering knowledge is lacking, then how to internalize PAI material to the affective and psychomotor realms in students if the cognitive aspects alone fail to be conveyed. This study aims to explain the actualization of PAI teachers who master Arabic literacy. The research method used is qualitative research with literature studies. The findings show that teaching PAI material requires passion and soul. Especially when explaining Arabic terms. Teachers who read and explain the translation only in the book when teaching PAI, the learning process will feel dry due to lack of meaning. Because PAI material is closely related to Arabic terms, the Arabic literacy ability of PAI teachers is very important to have as a form of self-actualization when teaching PAI material.